Pengaruh Penambahan Core Stability Exercise Terhadap Peningkatan Kebugaran Jasmani A (Daya Tahan)pada Prajurit Militer Brigif 15 Kujang II Cimahi - Oktaviyani, Feny; Arifin, Jenal (CV RIFAINSTITUT, 2021)
Physical fitness is the body's ability to carry out physical activities without causing excessive fatigue. For a military soldier, physical fitness plays an important role in improving and maintaining the military body, in order to support the implementation of the main tasks of military soldiers. Physical fitness can be optimized, one of which is the core stability exercise. This study aims to analyze the effect of adding core stability exercise to increase physical fitness A (endurance) in military soldiers at Brigif 15 Kujang II Cimahi. A quasi-experimental study with a pre-post two group design approach consisting of an experimental group and a control group. With purposive sampling technique, 48 people were selected which were divided into two groups, namely the experimental group (n=24) and the control group (n=24). The experimental group was given a 12-minute running exercise program and core stability exercise while the control group was only given a 12-minute running exercise and data collection in the form of a 12-minute running test. There was a difference in the mean physical fitness score A between the experimental group (Mean= 40.33; SD= 3.54) and the control group (Mean= 44.17; SD= 6.72) before the intervention, and the difference was statistically significant (p= 0.017). There was a difference in physical fitness scores before and after the intervention between the experimental group (Mean= 4.38; SD= 1.41) and the control group (Mean= 2.42; SD= 2.04) and statistically significant (p<0.001), with effect size = 1.14. Core stability exercise is effective to increase the value of physical fitness A in Brigif 15 Kujang II Cimahi soldiers.